An Exploration into the Reasons People Choose a Pastoral Counselor Instead of Another Type of Psychotherapist - Posavac, Emil. J. (The Journal of pastoral care, 1977)
The results of several approaches to understanding the laymen's perception of fulltime pastoral counselors are reported. No striking differences among the respondents' views of various types of psychotherapists were found. However, 20% of the clients of a pastoral counseling center gave clear religious reasons for choosing the center rather than seeking help from another source of therapy. Also important was the finding that the rate of clergy referrals to the center (about half of all clients) is far in excess of published clergy referral rates to psychiatrists, psychologists or psychoanalysts. The importance of ties between pastoral counseling centers and community parishes is stressed.